A systematic literature review of factor analytic and mixture models of ICD-11 PTSD and CPTSD using the International Trauma Questionnaire. (April 2021) - Redican, Enya; Nolan, Emma; Hyland, Philip; Cloitre, Marylene; McBride, Orla; Karatzias, Thanos; Murphy, Jamie; Shevlin, Mark
Highlights: Review of latent structure of International Trauma Questionnaire. Correlated six-factor and two-factor second-order most commonly supported symptom structures. Distinct classes representing PTSD and CPTSD symptom profiles have been reported in clinical and non-clinical samples. Validity PTSD and CPTSD supported when tested in conjunction with other variables. More research needed on populations with high rates of trauma exposure. Abstract: The 11th version of the International Classification of Diseases (ICD-11; WHO, 2018 ) describes two distinct trauma related disorders, Posttraumatic Stress Disorder (PTSD) and Complex PTSD (CPTSD). This review aims to summarise and synthesize evidence from factor analytic and mixture modelling studies that have investigated the latent structure of the International Trauma Questionnaire. A systematic search of PsycInfo, Web of Science, Scopus and Pubmed databases was conducted to identify relevant articles. Thirty-three studies met the inclusion criteria for this systematic review. The latent structure of the ITQ was best represented by two models; a correlated six-factor model (Re-experiencing, Avoidance, Threat, Affect Dysregulation, Negative Self Concept, and Disturbed Relationships) and a two-factor second-order model (PTSD and Disturbances in Self-Organization). Mixture model studies consistently identified distinct classes representing those displaying PTSD and CPTSD symptoms. Numerous studies demonstrated support for the factorial and discriminant validity of PTSD and CPTSD when analysed in conjunction with other variables. Overall, support was found for the conceptual coherence of PTSD and CPTSD as empirically distinguishable disorders, as measured by the ITQ. The available evidence demonstrates that the ITQ is a valid measure of ICD-11 PTSD and CPTSD. Recommendations for future research are included.